Diet composition of expanding breeding populations of the Magellanic Penguin. Issue 1 (2nd January 2019) - Fernandez, Santiago José; Yorio, Pablo; Ciancio, Javier Ernesto
ABSTRACT: The Magellanic Penguin ( Spheniscus magellanicus ) is the most abundant and widely distributed seabird breeding on the Patagonian Coast of Argentina. We combined conventional stomach content and stable isotope analysis to assess Magellanic Penguin diet during the chick rearing stage at the two northernmost colonies in an area subject to fisheries. In 2011 and 2013, Thornfish ( Bovichtus argentinus ) was the main prey by mass at Complejo Islote Lobos (63.0% and 32.3%, respectively) and Argentine Anchovy ( Engraulis anchoita ) at Estancia San Lorenzo (85.2 and 63.3%, respectively). Magellanic Penguins from both colonies showed low isotopic niche overlap in 2011 (36%) and no overlap in 2013, suggesting a different use of prey species and/or foraging areas. Stable isotope mixing models showed that Argentine Anchovy (52.8%) and Thornfish (65.9%) were the main prey at Complejo Islote Lobos in 2011 and 2013, respectively, while Patagonian Redfish ( Sebastes oculatus ) (46.4%) and Squat Lobster ( Munida gregaria ) (50%) were the main prey at Estancia San Lorenzo in 2011 and 2013, respectively. Results show that in addition to Argentine Anchovy, previously recognized as main prey for breeding Magellanic Penguins in northern Patagonia, other juvenile or small sized fish are important diet items. Diet results suggest different scenarios of food conditions for each colony, despite the relative short distance between breeding locations. The low contribution of Argentine Hake ( Merluccius hubbsi ) and Argentine Shortfin Squid ( Illex argentinus ) suggests a low trophic overlap with commercial fisheries. The information provided is key to understand changes in the marine ecosystem and potential penguin-fishery interactions.